PENGARUH KEPEMIMPINAN PARTISIPATIF, KOMITMEN ORGANISASIONAL DAN IMBALAN FINANSIAL TERHADAP KEPUASAN KERJA KARYAWAN - Bagus Sugihandara, IGN; Supartha, I Wayan Gede (E-Jurnal Manajemen; Vol 4 No 10 (2015), 2015)
Villa is one of the service industries that provide lodging services to the increasingly fierce competition, it would require the support of competent human resources in order to compete. The aim of this study is to analyze and explain the influence of participative leadership, organizational commitment and the financial rewards on employee job satisfaction at Maca Villa & Spa, Seminyak Bali. The location of this research is Maca Villa & Spa, Seminyak Bali with data processing techniques based on confirmatory factor analysis and multiple linear regression. Through census method the number of samples taken by 46 respondents. The research proves that participative leadership, organizational commitment and financial rewards have influence accuracy of 84.5%, while the remaining 15.5% is influenced by other factors not examined. Participatory leadership, organizational commitment and financial rewards positive and significant impact on job satisfaction partially. Participative leadership is the variable that most affect employee satisfaction Maca Villa & Spa, Seminyak Bali.
Keywords: participative leadership, organizational commitment, financial rewards and job satisfaction